Pengaruh Penambahan SCES Terhadap Peningkatan Kestabilan Transien Menggunakan Metode Critical Trajectory Berbasis Losing Synchronism - Priyadi, Ardyono; Riambodo, Arief; Puspita Sari, Talitha; Soedibyo, Soedibyo (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2020)
Three phase fault is one of a transient phenomenon that must be isolate immediately to prevent losing synchron of generator in power plant, so that the system remain stable. Critical clearing time is maximum time allowed to isolate the system fault so that the system remain stable. Super capacitor energy storage installation to the system is one way to improve CCT value. Super capacitor is one of energy storage that be able to supply and store large amounts of electricity power quickly. Super Capacitor can improve CCT value by muffle oscillation of 3 phase fault. With higher CCT value, then time operation of protection system can be longer. The result is the system remain stable after fault removed and it can be improve transient stability in power system. Within an optimal sizing of super capacitor capacities for the system, then the value of CCT that obtained is higher than protection time operation. So that in this final project will be carried out an optimal sizing of super capacitor for improving transient stability with critical trajectory based on losing synchronism method